Investigation of SAR Reduction and Bending Effect Using a Flexible Antenna with EBG Structure for 2.45 GHz Wearable Applications - Nilesh Kasat, Sonal Jatkar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents, an analysis of Co-Planar Waveguide fed textile antennas operating at 2.45 GHz frequency with an Electromagnetic Band-Gap array for WBAN applications. Denim substrate, characterized by its dielectric constant of 1.6 and thickness of 1mm which is stacked together to get height of 3mm. Simulation using HFSS provides a return loss of -52 dB at 2.45 GHz. Size of antenna after incorporating 2*2 array in EBG structure is 61*61*3 mm3. It results in increase gain from 2.36 dB to 4 dB without EBG and with EBG respectively. Stochastic frameworks employing polynomial chaos principles expansions is used to model antenna dimensions. The study aimed to investigate how bending affects antenna performance, employing two bending scenarios: one in the H plane and the other in the E plane. Also, for WBAN applications, SAR value is simulated on human body phantom using HFSS simulator and is obtained to 41.04 W/Kg without EBG and 0.522 W/Kg with EBG.